Morphological Characterization of Ectoparasites Infestating Dogs from an Animal Birth Control Campaign in Khotang, Nepal - Pathak, Chet Raj (Journal of Agriculture and Forestry University, 2025)
Dogs are an integral part of human civilization as companion animal species. But free-roaming dogs create major veterinary and public health concerns due to their role as reservoirs of ectoparasites and vector-borne pathogens. In Nepal, Himalayan Sheepdogs (Bhote Kukur) are culturally significant but poorly studied regarding ectoparasitic infestations. This study was conducted during an animal birth control campaign for dogs (N = 105) in July 2025 at Diktel Rupakot Majhuwagadhi Municipality, Khotang District. Ticks were collected by handpicking/forceps, preserved in 70% ethanol, and identified morphologically under a stereo zoom dissecting microscope using standard taxonomic keys. Morphometric analyses were based on diagnostic features of ticks (capitulum, scutum, spiracles), fleas (combs), and flies (wing venations). Overall, 147 ectoparasites recovered where ticks were most prevalent (25.71%), followed by fleas (2.85%), and flies (0.95%) in dogs, with occasional mixed infestations. Identified species included brown ticks (Rhipicephalus sanguineus and R. haemophysaloides), flea (Ctenocephalides canis), and louse fly (Hippobosca longipennis). The predominance of ticks, particularly females, underscores their role as vectors of pathogens such as Ehrlichia, Babesia, and Anaplasma. This study provides the first baseline on ectoparasites of Himalayan Sheepdogs in rural Nepal and emphasizes the need for integrated conventional and advanced molecular diagnosis and control strategies for strengthening One Health approach.